Local monitoring techniques for cultural heritage sites affected by geo-hazards - Themistocleous, Kyriacos (My University, 2018)
PROTHEGO (PROTection of European Cultural HEritage from GeO-hazards) uses novel space technology to monitor surface deformation with mm precision to analyze the impact of geohazards in cultural heritage sites in Europe. The project includes the 395 monuments of UNESCO in Europe to monitor geo-hazards, with case studies conducted in 4 UNESCO sites in England, Spain, Italy and Cyprus. The PROTHEGO project uses long-term low-impact monitoring systems, such as UAVs and geodetic techniques, as well as InSAR data to monitor and assess the risk from natural hazards on the archaeological site to evaluate potential geo-hazards. Locale scale monitoring provides the opportunity to detect and analyze deformation phenomena for monitoring and predicting geo-hazards using field survey techniques to measure and document the extent of damage of the natural hazard on the cultural heritage site. The geodetic techniques can be used in combination with UAVs for documentation purposes and 3D modeling comparison. The aerial imagery obtained from the UAVs can be processed to create 3D model in order to document and monitor the extent of geo-hazards at the cultural heritage site. The ground based geotechnical monitoring can then be compared and validated with InSAR data to evaluate cultural heritage sites deformation trends. The PROTection of European Cultural HEritage from GeO-hazards (PROTHEGO)" project HERITAGE PLUS/0314/36 is funded in the framework of the Joint Programming Initiative on Cultural Heritage and Global Change (JPICH)-HERITAGE PLUS under ERA-NET Plus and the Seventh Framework Programme (FP7) of the European Commission and the Cyprus Research Promotion Foundation, contract KOINA/Î ÎšÎ-HERITAGE PLUS/0314/36.
Keywords: Aerial photography; Hazards; Remote sensing; Archaeological site; Cultural heritages